2005
DOI: 10.2337/diacare.28.4.806
|View full text |Cite
|
Sign up to set email alerts
|

Use of HLA Typing in Diagnosing Celiac Disease in Patients With Type 1 Diabetes

Abstract: OBJECTIVE—This study examines the use of HLA typing for the diagnosis of celiac disease in a group of Australians with type 1 diabetes. RESEARCH DESIGN AND METHODS—Subjects included 131 sequential patients with type 1 diabetes (mean age 17 years [range 10–37]), 77 patients with biopsy-proven celiac disease (mean age 52 years [range 12–84]), and 162 healthy control subjects (mean age 17 years [range 2 months to 56 years]). Subjects were prospectively screened for celiac disease using endomysial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
22
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 19 publications
8
22
0
2
Order By: Relevance
“…Another study by Doolan et al (43) showed increased DQB1Ã0201-DQA1Ã05 frequency in T1DM patients with CD (77%) compared with patients with T1DM only (59%), but the difference was not statistically significant. A limitation of these studies was the small number of patients with CD and T1DM.…”
Section: Discussionmentioning
confidence: 92%
“…Another study by Doolan et al (43) showed increased DQB1Ã0201-DQA1Ã05 frequency in T1DM patients with CD (77%) compared with patients with T1DM only (59%), but the difference was not statistically significant. A limitation of these studies was the small number of patients with CD and T1DM.…”
Section: Discussionmentioning
confidence: 92%
“…O anticorpo antitransglutaminase tecidual humana IgA tem sido recomendado como o de escolha (10) por apresentar sensibilidade superior ao antiendomísio IgA, não obstante a especifi cidade semelhante. Para evitar o encontro de falso-negativos para estes anticorpos, é recomendada a verifi cação dos níveis séricos de IgA durante o rastreamento (10,13). Aqueles pacientes que apresentam sorologia positiva devem ser submetidos à endoscopia digestiva alta com biópsia de intestino delgado para a confi rmação da doença.…”
Section: Discussionunclassified
“…The CD prevalence in the general population of all ages is 0.3%–1.0%11 whereas in patients with T1D it ranges from 1.6% to 16.4% in children4 12 13 and 6.0% in adults4 and varies between populations from 6.2% (Sweden),14 8.4% (Australia)15 up to 10.0% reported in ISPAD guidelines16 and 12.0% reported for Europe by the European Society for Paediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN) group 17. Being aware of the association between CD in patients with T1D and the fact that the classical intestinal symptoms may be missing in this risk group, the recommendation of paediatric endocrinologists involves active case identification by antibody screening tests performed annually using anti-tissue transglutaminase (TG) two in the first instance followed by anti-endomysial antibody (EMA)18 as they help to confirm diagnosis of CD due to >99% specificity 19.…”
Section: Introductionmentioning
confidence: 99%